Novelty, Challenge, and Practice: The Impact of Intensive Language Learning on Attentional Functions. - Thomas H Bak; Madeleine R Long; Mariana Vega-Mendoza; Antonella Sorace (PLoS ONE)
We investigated the impact of a short intensive language course on attentional functions. We examined 33 participants of a one-week Scottish Gaelic course and compared them to 34 controls: 16 active controls who participated in courses of comparable duration and intensity but not involving foreign language learning and 18 passive controls who followed their usual routines. Participants completed auditory tests of attentional inhibition and switching. There was no difference between the groups in any measures at the beginning of the course. At the end of the course, a significant improvement in attention switching was observed in the language group (p < .001) but not the control group (p = .127), independent of the age of participants (18-78 years). Half of the language participants (n = 17) were retested nine months after their course. All those who practiced Gaelic 5 hours or more per week improved from their baseline performance. In contrast, those who practiced 4 hours or fewer showed an inconsistent pattern: some improved while others stayed the same or deteriorated. Our results suggest that even a short period of intensive language learning can modulate attentional functions and that all age groups can benefit from this effect. Moreover, these short-term effects can be maintained through continuous practice.